PRESIDEN MEMBAWAHKAN KEPOLISIAN NEGARA - H. Eko Sugitario (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2018)
State Constitution of 1945, Republic Indonesia, herein after called Conti.titution 1945 and be concised UUD 1945. Article 10 determine that "President holds 9 highest authority of-·infantry, navy, and air force. On the dated of first July, 1946 determined Government decision number l//SD/1946 about Formation of State Police Division. in the decision mention above also be determined that State Police responsible directly to Ministery up to now on first July known as Bhayangkara day. After revalidated UUD 1945, based on Dekrit Presiden 1959,_ so determined ordinance number 13 year 1961 about Main Decisions of State Police, that in article 6 determined "President holds a highest authority of state police". Before that, also it has President decision number 21 year 1960 which the content is, to hold or form Ministery's duty/ Head of State Police. Based on article 10 UUD 1945 and article 6 ordinance number 13 year 1961, so President holds a highest oj infantry, navy and air force, also state police. Then,-ordinance number 13 year 1961 had been changed with ordinance number 28 year 1997 about State Police Republic indonesia, in article 8 (1) determined that" State Police of Republic Indonesia under President". Therefore, based on ordinance number 13 year 1961, ordinance number 28 year 1997, and ordinance number 2 year 2002 are very clear that President is in charge to State Police of Republic Indonesia.